Sphecidae y crabronidae (hymenoptera) de algunos municipios del centro y sur de Tamaulipas, México - Horta Vega, Jorge Víctor; Pinson Domínguez, Oswaldo Noel; Barrientos Lozano, Ludivina; Correa Sandoval, Alfonso (Instituto de Ecología, A.C., 2007)
One hundred and twenty four species and forty four genera of sphecoid wasps collected at localities of eleven municipalities of Tamaulipas, Mexico were recorded. Twenty three species and three genera are new records for the country meanwhile 94 species and 26 genera are new records for the state of Tamaulipas. Crabronidae and Sphecidae comprise 98 and 26 species respectively. The most abundant species were Ammophila picipes and Trypoxylon (Trypargilum) spinosum. Ammophila picipes is the most widely distributed species. From the 103 genera and 658 species recorded in Mexico 54 genera (52%) and 142 species (21.6%) have been found in Tamaulipas.